A utilitarian notion of responsibility for sustainability - Joachim Fünfgelt; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
We develop and formalize a utilitarian notion of responsibility for sustainability which is inspired by Singer's (1972) principle and the Brundtland Commission's notion ofsustainability (WCED 1987). We relate this notion of responsibility to established criteria forthe assessment of intertemporal societal choice, namely Pareto-efficiency, (discounted) utilitarian welfare maximization, and Brundtland-sustainability. Using a two-generationsresource-model, we find the following. Sustainability and responsibility for sustainability are equivalent if and only if sustainability is feasible. If it is not, there still exists a responsible allocation which is also Pareto-efficient. Further, the utilitarian welfare maximum without discounting always fulfills the criterion of responsibility. Discounting may be responsible to a certain extent if sustainability is feasible. If sustainability is not feasible, discounting is not responsible.
Keywords: D63; D90; Q01; G56; 330; basic needs; Brundtland; discounting; ethics; natural resources; Pareto efficiency; responsibility; Singer; sustainability; utilitarianism; Nachhaltige Entwicklung; Verantwortung; Utilitarismus; Grundbedürfnisse; Abzinsung; Pareto-Optimum; Theorie